(untitled) (Revista Educação, Artes e Inclusão, 2022)
Ballroom dancing has grown in demand recently. The students’ profiles are the most varied, which implies the teachers’ pedagogical practice. This article, in addition to problematizing the question of the methods of teaching ballroom dancing (LIBÂNEO, 1999; SANTOS, 2009; GRANGEIRO, 2014; ZAMONER, 2005), in na unprecedented way, presentes a teaching method, entitled “- Steps, + Dance”, which was structured by the first author of this article, being implemented in a ballroom dance class in the Southern Brazil. Among its main features are: working more than one dance style per class, not using the mirror, constant Exchange of pairs and students from diferente periods of learning time are part of the same class. A survey of sources on the subject was made, in addition to a semi-structured interview with twelve apprentices who had contact for at least six months, with the proposal used in ballroom dance classes. The results point to a significant adaptation of the students with the method “- Steps, + Dance” that reverberated not only in learning of new body techniques, but also in new opportunities for social relationships and new ways of reflecting on the world.